Social Ancient Rarity Improvement as Rustic The Travel Industry, Contextual analysis: The village of Siangan, Gianyardistrict – Indonesia - Kurniawan, Agus; Runa, I Wayan; Wandira, I Wayan Mariyana (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Traditional Siangan Traditional Village can be found 31 kilometers northeast of Denpasar City. As a spiritual tourism village, this village has cultural potential that can be developed. Seven ancient sites, natural beauty, local art, and cultural traditions can all be used as tourist attractions in Siangan Traditional Village. The indigenous village krama community has not fully appreciated the potential of existing cultural heritage to be used as a starting point for spiritual tourism. To support the tourism growth of Siangan Village, community empowerment is needed to inventory heritage in the form of cultural artifacts and their use as tourist attractions. Yayasan Sentir Bali as a partner in the Community Partnership Program (PKM) is expected to be able to face the following problems: (1) the inventory of all cultural heritage in Siangan Traditional Village, (2) the historical background of cultural heritage in Siangan Village, and (3) the unused cultural heritage as a spiritual tourism base. By conducting an inventory of cultural heritage in Siangan Traditional Village and managing cultural heritage as a tourist attraction, this PKM is a form of community empowerment in the use of cultural heritage. Structuring as a foundation for spiritual tourism. Archaeological documentation techniques and public archaeology approaches are used in the implementation of cultural heritage management models. Partners together with communities will recognize the importance of cultural heritage as the foundation of spiritual tourism, which has implications for goodness-being a community, as a result of this strategy.